Preference-based Accommodation Strategy design and decision approach - Monique Arkesteijn (A+BE: Architecture and the Built Environment)
One of the long-standing issues in CREM is the alignment of an organization’s real estate to its corporate strategy as I have shown in chapter 2. CRE alignment is even defined by some as the raison d’être of CREM, as the range of activities undertaken to attune corporate real estate optimally to corporate performance. Even though extensive research into existing CRE alignment models has provided us with valuable insights into the steps, components and variables that are needed in the alignment process, these models still fall short in two ways. Most models pay little to no attention to the design of a new portfolio and to the selection of a new portfolio that adds the most value to the organization.